Survival of Gram-Negative Bacteria on Plastic Compounded with Hexachlorophene - Taylor, Gerald F. (1970)
Gram-negative bacteria representing nine genera were screened for their ability to survive surface exposure to polyethylene sheet plastic containing chemically compounded hexachlorophene (0.25%). Subcultures were made at hourly intervals over a 6-hr period of time. An exceedingly large drop in viable cells beginning at the 1-hr exposure was noted for each genus except one tested on the hexachlorophene-plastic, whereas most nonadditive controls grew bacterial colonies too numerous to count.